Study of the properties of SiOx layers prepared by different techniques for rear side passivation in TOPCon solar cells. (15th November 2020) - Chandra Mandal, Nabin; Biswas, Susmita; Acharya, Shiladitya; Panda, Tamalika; Sadhukhan, Sourav; Sharma, Jayasree Roy; Nandi, Anupam; Bose, Sukanta; Kole, Arindam; Das, Gourab; Maity, Santanu; Chaudhuri, Partha; et al.
Abstract: Passivation of n-type and p-type monocrystalline CZ Si wafers (both polished and textured) with silicon oxide layers prepared by thermal (TO), chemical (CO) and plasma (PO) techniques have been extensively investigated from the measurement of minority carrier lifetime (τ) by transient electrical photoresponse method, density of interface states (NSS ) measurement by capacitance – voltage study and silicon oxidation states by X-ray photoelectron spectroscopy (XPS) study of the SiO2 /Si interface. It has been observed that NSS and τ have an inverse relation but the dependence is not linear. The method (TO, CO or PO) of oxide layer development has been found to play a crucial role to control the passivation of the c-Si wafer surface. It has been observed that the thermally grown oxide layer (TO) is superior among three oxide layers for all the different c-Si surfaces. Very low density of interface states (<5 × 10 11 ) were found in both p-type and n-type polished wafer passivated with TO layer. Highest lifetimes of 170 μs for n-type polished wafer and 102.74 μs for p-type polished wafer were obtained with TO. The amount of sub oxide formed at the interface of both n- and p-type of wafers during different oxidation process, may have some correlation with Nss which in turn determines the passivation quality of the wafers. Improvement of implied Voc for both polished and textured wafers (n-type and p-type) was found using thermally grown oxide with respect to others.